1967
DOI: 10.1083/jcb.34.2.647
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Human Oocyte and Its Follicle

Abstract: Oocytes in primordial ("resting") follicles in adult human ovaries contain a complex paranuclear structure identified by light microscopists as Balbiani's vitelline body. By electron microscopy this structure is composed of a mass of mitochondria with associated endoplasmic reticulum, multiple compound aggregates which form a ring around the cytocentrum, and a single stack or coil of annulate lamellae either attached to the nuclear membrane or free in the cytoplasm. The compound aggregates contain vacuoles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
2

Year Published

1973
1973
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(69 citation statements)
references
References 27 publications
8
59
0
2
Order By: Relevance
“…In general, the ultrastructure of goat preantral follicles was similar to that of other mammalian species (cattle - Van Wezel and Rodgers, 1996, Fair et al, 1997bpig -Greenwald and Moor, 1989;feline -Jewgenow and Stolte, 1996;humanHertig andAdams, 1967 andOktay et al, 1997), but some differences were observed, which may indicate either species specific differences or different phases of follicular development.…”
Section: Discussionsupporting
confidence: 55%
“…In general, the ultrastructure of goat preantral follicles was similar to that of other mammalian species (cattle - Van Wezel and Rodgers, 1996, Fair et al, 1997bpig -Greenwald and Moor, 1989;feline -Jewgenow and Stolte, 1996;humanHertig andAdams, 1967 andOktay et al, 1997), but some differences were observed, which may indicate either species specific differences or different phases of follicular development.…”
Section: Discussionsupporting
confidence: 55%
“…Those that survive this process are ovulated and undergo the final phases of maturation that prepare the nucleus and cytoplasm for embryogenesis. Throughout oogenesis in mammals, oocytes maintain physical contact with follicular somatic cells via granulosa cell extensions known as transzonal projections (TZPs) [1,6,23,33,43,44]. Despite the recognized functions of TZPs in gap junction mediated metabolite exchange, heterocellular adhesion, cell cycle regulation and bidirectional signaling [10,18,40,47], the precise role these structures play in the acquisition of developmental competence during oocyte maturation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…6A). The location of this body corresponds to the so-called ''yolk nucleus'' of Balbiani's vitelline body, described ultrastructurally in detail by Hertig and Adams (22) in human primordial follicles. Immunostaining of this body was not observed with preimmune sera or antisera to other ovarian antigens such as inhibin and depended on the presence of primary antibody (data not shown).…”
Section: Generation Of Antibodies and Immunohistochemical Analysis Ofmentioning
confidence: 99%